Mixing with native broadleaf trees modified soil microbial communities of Cunninghamia lanceolata monocultures in South China - Zheng, Fenglin; Gu, Jiawei; Lu, Dehao; Yang, Jiaman; Shuai, Xiaomai; Li, Cheng; Chen, Hongyue (Frontiers in Microbiology, 2024)
Mixing with different broadleaf trees into the monocultures of Cunninghamia lanceolata is widely adopted as an efficient transformation of the pure C. lanceolata forest. However, it is unclear how native broad-leaved trees influence the belowground ecological environment of the pure C. lanceolata culture plantation in nutrient-poor soil of South China. Herein, we aimed to investigate how a long-time mixing with native broadleaf trees shape soil microbial community of the pure C. lanceolata forest across different soil depth (0–20 cm and 20–40 cm) and to clarify relationships between the modified soil microbial community and those affected soil chemical properties. Using high-throughput sequencing technology, microbial compositions from the mixed C. lanceolata-broadleaf forest and the pure C. lanceolata forest were analyzed. Network analysis was utilized to investigate correlations among microorganisms, and network robustness was assessed by calculating network natural connectivity. Results demonstrated that the content of soil microbial biomass carbon and nitrogen, total phosphorus and pH in mixed forest stand were significantly higher than those in pure forest stand, except for available phosphorus in topsoil (0–20 cm). Simultaneously, the mixed C. lanceolata-broadleaf forest has a more homogeneous bacterial and fungal communities across different soil depth compared with the pure C. lanceolata forest, wherein the mixed forest recruited more diverse bacterial community in subsoil (20–40 cm) and reduced the diversity of fungal community in topsoil. Meanwhile, the mixed forest showed higher bacterial community stability while the pure forest showed higher fungal community stability. Moreover, bacterial communities showed significant correlations with various soil chemical indicators, whereas fungal communities exhibited correlations with only TP and pH. Therefore, the mixed C. lanceolata-broadleaf forest rely on their recruiting bacterial community to enhance and maintain the higher nutrient status of soil while the pure C. lanceolata forest rely on some specific fungi to satisfy their phosphorus requirement for survive strategy.